Gaudium et Spes: Voltando ao texto e apontando luzes para a presença cristã na sociedade contemporânea - Rodrigues Ferreira, Reuberson (Kairós: Revista Acadêmica da Prainha, 2021)
This article revisits the Constitution Gaudium et Spes. The research seeks to identify from that document lights for the active presence and responsible of the Christian and the Church in contemporary society. The methodological steps to achieve is the purpose will be biobibliográfica review. Thus, it appears, first, the historical construction of the Pastoral Constitution Gaudium et Spes on the Church in the world today. Similarly, the elements of the discussion accompanying their preparation. Then the structure of the document and its main accents is demonstrated. Finally, we present some challenges of modern society are scored so that the light of the Pastoral Constitution ways is discussed to the Christian presence in contemporary society